Scientific Methods and Sacred Matters: On Methodological Naturalism, Divine Agency, and Christians in Science. - Mallary, Mitchell (Zygon: Journal of Religion & Science, 2024)
This article critically analyzes the debate surrounding methodological naturalism (MN) within the context of scientific inquiry, focusing on the arguments put forth by Andrew Torrance on the one hand and John Perry and Sarah Lane Ritchie on the other. It begins with the medical mystery known as the spontaneous remission of cancer--sometimes identified as a "miracle"--posing the question of how Christian medical researchers should approach this anomaly. Thereafter, I consider how Torrance's rejection of MN, due to its perceived conflict with faith, would expect the Christian scientist to respond. Conversely, Perry and Ritchie defend MN, emphasizing its importance in maintaining scientific rigor and avoiding a "God of the gaps" approach. Subsequently, I demonstrate how both science and MN are conceived of differently between the two parties, indicating that this is primarily a semantic debate. Finally, after examining Torrance's response to Perry and Ritchie, I propose a more nuanced approach, advocating for methodological flexibility wherein the nature of the question being asked determines the appropriate method one should employ.